The relationship between physical exercise and subjective well-being among Chinese junior high school students: A chain mediating model - Shu-Jun Yao; Qi-Shuai Ma; Chao Liu; Da-Wei Cao; Da-Wei Cao; Teng Lyu; Ke-Lei Guo (Frontiers in Psychology, 2023)
ObjectiveThis study aims to help understand the mechanism behind the relationship between physical exercise and the subjective well-being among Chinese junior high school students, and it is of great significance for the intervention measures to improve the subjective well-being of junior high school students.MethodsUsing stratified cluster sampling method, 1,510 junior high school students (727 males and 783 females) were measured by physical exercise rating scale, perceived social support scale, physical exercise self-efficacy scale, and subjective well-being scale. For data analysis, Pearson’s correlation analysis, structural equation model test, and bias-corrected percentile Bootstrap method were carried out in turn.ResultsCommon method biases can be accepted in this study. (1) There is a positive correlation between physical exercise and subjective well-being, and physical exercise has a significant predictive effect on subjective well-being(β = 0.367 t = 9.415 p < 0.01); (2) Perceived social support partially mediated the relationship between physical exercise and subjective well-being (β = 0.08, t = 3.083, p < 0.01), and its effect ratio is 78.047%; (3) Physical exercise self-efficacy plays a partial mediating role between physical exercise and subjective well-being(β = 0.181, t = 5.132, p < 0.01), accounting for 50.632%; (4) The chain mediating effect of perceived social support and physical exercise self-efficacy was significant (the mediating effect value was 0.028), and the effect amount was 7.629%.Conclusion(1) Physical exercise can significantly positively predict the subjective well-being of junior high school students; (2) Physical exercise can also indirectly affect the subjective well-being of junior high school students through the mediating effect of perceived social support and physical exercise self-efficacy. The intermediary effect includes three paths, namely, the individual intermediary effect of perceived social support and physical exercise self-efficacy and the chain intermediary effect of perceived social support physical exercise self-efficacy.